PELAKSANAAN INFORMED CONSENT TERHADAP BERLAKUNYA TRANSAKSI TERAPEUTIK DI RUMAH SAKIT DIRGAHAYU SAMARINDA - Kuswanto Kuswanto (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstractIn World Medical, information is the right of the patient as stipulated in Law no. 36 of 2009 on Health, as based on the information that was then the patient can make a decision about a medical action undertaken against him, on the other hand provide proper information to the patient, is the principal obligation of a doctor who was carrying out his profession.A doctor can not guarantee that he would be able to cure the patient, as a result of treatment is dependent upon many factors related, thus, the agreement between the patient's physician was legally incorporated into the class agreement (inspanningsverbintenis). The relationship between doctor and patient, legally generally occurs through a transaction that is initiated by therapeutic questioning and obtained provisional diagnosis between doctors and patients later followed by a physical examination, the doctor finally establish a diagnosis.